Branding Innovation: The Improvement of Small & Medium Enterprises in Desa Sulahan for Specific Commodities - Utami, Ni Made Widyaningtyas Dwi; Putri, Dewa Ayu Putu Adhiya Garini (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Sulahan Village is a village that has so much potential, one of which is the upakara or banten snack production house located in the Lumbuan Traditional Village area. The production of upakara snacks has been going on for quite a long time from several previous generations that have been passed down to the present. The purpose of this Real Work Lecture program is to find out how to advance the potential of MSMEs through the application of branding to Upakara Bali Snack MSMEs. The methods used are field observation, interviews, and the application of useful ideas. The result of this community service is in the form of empowerment which aims to make the Upakara Snack MSME business grow and have a wider reach by means of effective and efficient branding, which is expected to increase sales to Upakara Snack MSMEs in Sulahan Village, precisely Lumbuan Traditional Village. For this reason, at the end of this activity, it is hoped that the owner will be able to understand and be able to further expand the marketing reach. Upakara Snack MSMEs can be more innovative and can even compete with existing opportunities.